The Effectiveness of Social Media Influencers and Its Impact Digital Marketing Towards the Buying Behaviors among Generation Z in Malaysia - Tan, Kristine, Kai Qing; Soon, Eu Hui; Phung, Siew Poh (INTI International University, 2024)
The increasing number of active social media users has given rise to a new form of digital marketing and claims refer to heightened effects with the presence of social media influencers. This strategy leverages individuals with established online identities and reputations to promote products or brands through posts, photos, and videos, shaping consumer perceptions and behaviors. Recognizing its potential, many companies and brands have adopted this approach, particularly when targeting Generation Z. This study aims to determine the effectiveness of social media influencers and their impact on the buying behaviors of Generation Z in Malaysia. Data was collected through an online survey distributed via Google Forms, yielding 120 valid responses, which were analyzed using SPSS software. The findings indicate significant relationships between the variables examined, with all hypotheses supported, revealing that social media influencers positively and effectively impact the purchasing decisions of Generation Z. Furthermore, this research underscores the importance of collaboration between businesses, influencers, and digital platforms to foster sustainable partnerships in digital marketing, aligning with Sustainable Development Goal 17 (SDG 17). By promoting ethical and mutually beneficial partnerships, this study advocates for a more inclusive and sustainable approach to leveraging social media influencers in digital marketing strategies.